Development and Reliability and Validity Test to the Parenting Stress Questionnaire for Two-Child Mothers - Zhang, Zhinuo; Tang, Yulong; Chen, Xiyue; Lin, Xinyi; Tao, Jiaheng (Frontiers in Psychology, 2022)
China is getting old before it gets rich. Among women of childbearing age, there seems to be little interest in having multiple children, and parenting stress may be one of the reasons. There are differences in the parenting stress felt by mothers with one child and those with two, but there is no questionnaire specifically aimed at the parenting stress felt by mothers of multiples in China. The purpose of the present study is to develop and verify a questionnaire specifically aimed at measuring the stress of two-child mothers in the Chinese context. We chose mothers as participants who were younger than 50 years old and their second child were younger than 18 years old as participants. The initial questionnaire was created after analyzing the results of 83 participants’ open questionnaires and 16 participants’ qualitative interviews. Item analysis and exploratory factor analysis were conducted with 279 participants. The final questionnaire was created after conducting reliability and validity tests on the responses of 263 participants to 23 items on the questionnaire covering four factors: characteristics of mother, environmental factor, characteristics of child, and relationship between the two siblings. The results of confirmatory factor analysis indicated that the four-factor model fit well (χ2/df = 2.00, CFI = 0.91, TLI = 0.90, SRMR = 0.06, RMSEA = 0.06). McDonald’s omega coefficients and split-half reliability coefficients both ranged from 0.50 to 0.95. The questionnaire scores were significantly positively correlated with parental burnout, the regret of having a second child and parenting stress, and were significantly negatively correlated with the intention of having a third child and support for the three-child policy. Overall, the present study confirmed the reliability and validity of the parenting stress questionnaire for two-child mothers, which can be used to measure the parenting stress experienced by mothers of multiples in China.